2022
DOI: 10.1002/jhbp.1286
|View full text |Cite
|
Sign up to set email alerts
|

P53 immunolabeling in EUS‐FNA biopsy can predict low resection rate and early recurrence in resectable or borderline resectable pancreatic cancer treated with neoadjuvant therapy

Abstract: Purpose KRAS, P16, TP53, and SMAD4/DPC4 mutations are common in pancreatic ductal adenocarcinoma (PDAC). The study aimed to evaluate the association between gene mutations in pre‐treatment endoscopic ultrasound‐guided fine needle aspiration (EUS‐FNA) samples and clinical outcomes of patients with PDAC. Methods There were 43 patients with resectable (R) PDAC and 41 patients with borderline resectable (BR) PDAC. CDKN2A/p16, TP53, and SMAD4/DPC4 were evaluated through immunohistochemistry (IHC) of pretreatment EU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…We found a significantly higher rate of CDKN2A somatic mutations (52%) than described previously in LOPC (ICGC meta‐synthesis). At present, the relevance of this finding is uncertain because, at the protein level, loss of p16 expression in our EOPC cohort was comparable to that reported for PDAC in both age groups (commonly between 70% and 98%) [32,46,47,58].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…We found a significantly higher rate of CDKN2A somatic mutations (52%) than described previously in LOPC (ICGC meta‐synthesis). At present, the relevance of this finding is uncertain because, at the protein level, loss of p16 expression in our EOPC cohort was comparable to that reported for PDAC in both age groups (commonly between 70% and 98%) [32,46,47,58].…”
Section: Discussionsupporting
confidence: 62%
“…Immunohistochemistry results for p16, p53 and SMAD4 in our EOPC series were compared with the data from published reports where age of the patients was specified [4,[42][43][44][45][46][47]. The results are summarised in Table 3B and Table S6.…”
Section: Meta-synthesis Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Naito et al reported the first application of deep learning to detect adenocarcinoma in pancreatic EUS-FNB histological specimens based on training sets by expert pancreatic pathologists [ 62 ], and they noted that this approach yielded highly accurate diagnoses despite the complexity of the samples. Molecular subtyping of EUS-FNA/FNB specimens can also facilitate early diagnosis, with existing evidence suggesting the diagnostic and prognostic significance of testing samples for KRAS and TP53 mutations [ 63 , 64 ].…”
Section: Improvements To Current Diagnostic Approachesmentioning
confidence: 99%
“…According to Nitschke et al [70], mutant-KRAS detection in the peripheral blood, and even better, in the portal vein, is an independent adverse prognostic marker in curative and palliative PDAC patients and could be an effective novel tool for identifying prognostic borderline patients, guiding future decision making on NAT despite anatomical resectability. Oshima et al [71] evaluated the association between the three major genetic mutations (P16, TP53, and SMAD4/DPC4) associated with PDAC and their malignant behavior in 43 patients with resectable PDAC and 41 patients with BR-PDAC that underwent EUS-FNA before NAT. The three main genetic mutations were evaluated by immunohistochemistry both preoperatively in the EUS-FNA sample of 84 patients and in the resected PDAC sample of 71 patients, with 13 patients unresectable at the end of NAT.…”
Section: Ufs or Nat/nacrt (Neoadjuvant Chemoradiotherapy)?mentioning
confidence: 99%